2014
DOI: 10.1136/annrheumdis-2012-203187
|View full text |Cite
|
Sign up to set email alerts
|

Potential involvement of the IL-33–ST2 axis in the pathogenesis of primary Sjögren's syndrome

Abstract: IL-33 is released in pSS, and acts with IL-12 and IL-23 to favour the secretion of IFNγ by NK and NKT cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 16 publications
(18 reference statements)
4
43
0
2
Order By: Relevance
“…Two different studies have reported that serum levels of IL-33 and sST2 are higher in patients with pSS compared to those in healthy controls 25,26 , which was consistent with our results. However, we had some different observations in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Two different studies have reported that serum levels of IL-33 and sST2 are higher in patients with pSS compared to those in healthy controls 25,26 , which was consistent with our results. However, we had some different observations in our study.…”
Section: Discussionsupporting
confidence: 93%
“…IL-33 is a nuclear cytokine of the IL-1 family, which is constitutively expressed in epithelial barrier tissues and plays an important role in Th2 immunity [57]. Recently, increased IL-33 in the salivary glands and in serum have been linked to pSS [58]. Interestingly, in a murine model, it has also been shown that exposure of cigarette smoke upregulates IL-33 but simultaneously changes the immune response of IL-33 from Th2 to Th1 response [59].…”
Section: Discussionmentioning
confidence: 99%
“…The IL-33/ ST2 axis has been increasingly implicated in immunopathology and inflammation (Milovanovic et al, 2012). Blood levels of IL-33 are increased in a number of autoimmune and inflammatory (Milovanovic et al, 2012) diseases, such as rheumatoid arthritis (Kritas et al, 2013), systemic lupus erythematosus (Yu et al, 2013), Sjögren's syndrome (Awada et al, 2014), Grave's disease (Celik et al, 2013), and inflammatory bowel disease (Beltran et al, 2010). Genetic polymorphism studies have identified IL-33R1 as a susceptibility gene in inflammatory bowel disease (Jostins et al, 2012), Crohn's disease (Franke et al, 2010), and AD (Hirota et al, 2012).…”
Section: Functional and Pathologic Features Of Il-33 In Allergic Disementioning
confidence: 99%